Clays and Clay Minerals, Vol. 54, No. 3, 295-313, 2006. - Kister, Philippe; Laverret, Emmanuel; Quirt, David; Cuney, Michel; Mas, Patricia Patrier; Beaufort, Daniel; Bruneton, Patrice (The Clay Minerals Society, 2006)
The spatial distribution of the dominant matrix minerals present in the middle-Proterozoic Athabasca Group sandstone (kaolin, illite, sudoite, dravite, hematite) was studied at a regional scale in the Shea Creek region (Saskatchewan, Canada), in which two epigenetic unconformity-type uranium deposits have been discovered. 3D models of matrix mineral distribution were derived from normative mineral calculations and 3D interpolation using whole-rock geochemical analyses of sandstone samples collected from both mineralized and barren areas. The calculations were constrained by information obtained from petrographic and crystal-chemical clay mineralogical studies on representative samples. The 3D mineral distribution models were compared to the lithostratigraphy and structural features of the Athabasca Group sandstone to ascertain the source and mobility of the main elements involved in the sandstone host-rock alteration processes related to the U mineralization. The distribution of Al is conformable with the lithostratigraphy throughout the studied area, regardless of proximity to basement-rooted structures and U ore bodies. The distribution of illite displays similar features, but the intensity of the illitization of kaolin decreases with increasing distance from the structures and U ore bodies. Hematite bleaching and neoformation of sudoite and dravite were restricted to the vicinity of the fault zones above the U ore bodies. The spatial configurations of the mineral anomalies show that syn-ore fluids flowed from the basement towards the sandstone cover via the fault zones, as described in current metallogenic models. Although Al remained immobile (mass transfer), the anomalous K, B and Mg present in the host-rock alteration haloes were probably imported from the basement rocks (mass transport). Unlike B and Mg, K migrated laterally at least several kilometers from the basement-rooted faults. The mineral distribution models were used to quantify the volume of altered sandstone (10 ÿ2ÿ10 ÿ1 km3) and the amounts of K, Mg and B which were imported to the alteration haloes above the Shea Creek U ore bodies: 186,000 t of K, 66,000 t of Mg, and 11,000 t of B above the Anne ore body, and 24,000 t of K, 185,000 t of Mg, and a similar 11,000 t of B above the Colette ore body.
Mineralogy And Geochemistry Of The Host-rock Alterations Associated With The Shea Creek Unconformity-type Uranium Deposits (athabasca Basin, Saskatchewan, Canada). Part 2. Regional-scale Spatial Distribution Of The Athabasca Group Sandstone Matrix Minerals
gsccm-54-3-02-kis.pdf 2.09MB PDF/A Document.
Keywords: Periodicals; Geology; 3D Modeling; Athabasca Basin; Clay Minerals; Dravite; Host-rock Alteration; Illite; Kaolin; Normative Mineralogy; Unconformity-type Uranium Deposits; Sudoite